Wheel-turned Pottery in Yotvingian Hillforts - Baltramiejūnaitė, Dovilė (Archaeologia Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English] The application of wheel-turned technology in pottery production and its development among the Baltic people is little studied yet. The current paper is based on the archaeological material from the Užnemunė (Southwestern Lithuania) hillforts, which were investigated by P. Kulikauskas in the 1960s, and seeks to discuss the tendencies of how wheel-turned pottery had developed during the 10th–14th c. The materials in question derive from the northeastern part of the Yotvingian areal. Here, the suggested classification system is based on the possibly chronologically sensitive features of the pottery. They are distinguished after a detailed analysis of the technological, morphological and decorative attributes of the pottery in question. The classificatory units of pottery are dated in accordance with the contextual material as much as possible as well as in accordance with any similarities or analogies found in the closest archaeological sites. The identified stages of the development of pottery suggest a gradual mode of change, an improvement of the wheel-turned technology and a change of the forms and decorations. Even though there still is a lack of reliable absolute dates for the full reconstruction of the development of wheel-turned pottery in the northeastern Yotvingian areal, it is expected that a systematic approach to the material will lead to further studies and deeper knowledge.